Faktor Pemicu dan Penghambat Fraud dalam Program Jaminan Kesehatan Nasional dan Strategi Pencegahannya: Sebuah Scoping Review - Sam Tito, Julius; Siregar, Kemal Nazaruddin (UI Scholars Hub, 2024)
Fraud in the National Health Insurance program (JKN) has become one of the challenges faced by the government because it can harm the state finances and negatively impact the decline in the quality of health services. This research aims to identify triggering factors, inhibiting factors, and also strategies in preventing fraud in the JKN program. The study was conducted using the scoping review method according to the Arksey & O'Malley guidelines by searching 5 electronic databases and finding 2,622 articles. The literature search results were performed according to PRISMA-Scr, and 20 articles were analyzed in this study. The study results identified the triggering factors for fraud in the JKN program, namely the lack of understanding of the diagnosis system established by BPJS Kesehatan, dissatisfaction with the INA-CBGs system, insufficient internal supervision and control, limited resources and training for coding, financial factors, and behavioral and social factors. Meanwhile, the inhibiting factors for fraud in the JKN program include internal control, education and socialization, the implementation of SOPs and clinical pathways, as well as work culture and code of ethics. Fraud prevention strategies that can be implemented include strengthening internal controls, enhancing competencies and resources, formulating fraud prevention policies and guidelines, optimizing information technology in detecting fraud through the use of AI and machine learning, as well as reinforcing organizational culture and ethics.